Anatomic characterization of mentual foramen in dentate and edentulous regions with Cone Beam Computed Tomography (CBCT). - Lopes, Sergio Lucio Pereira de Castro; Donato, Iara Santos Quadros da Costa; Assis, Afonso Celso Souza de; Moraes, Mari Eli Leonelli de; Manhães Jr, Luiz Roberto Coutinho; Gamba, Thiago de Oliveria (Brazilian Dental Science, 2016)
Objective: To characterize and compare the positions and dimensions of the mental foramen (MF) openings between dentate and edentulous areas on cone beam computed tomography (CBCT) images. Material and Methods: Seventy-two CBCT images (i-CAT Next Generation, Imaging Sciences International, Hatfield, PA, USA) of the mandible were analyzed. The CBCT images were divided into two groups: Group D (dentate) - with first and second mandibular premolars; Group E (edentulous) - without first and second mandibular premolars. At the transversal cuts, two measurements were obtained: MF height – the vertical distance between the lowest point of the mandibular canal to the external cortical of the mandible’s base (MFIH); MF opening – the greatest vertical distance between the superior and inferior MF external corticals (AbMF). Also, in Group D, the MF position was studied in relation to four landmarks: 1st premolar, between 1st and 2nd premolar; 2nd premolar; and other locations. Independent sample t-test and descriptive analysis were applied. Results: Only the distance AbMF showed statistically significant difference between groups, with tendency towards increasing in group D. Group E exhibited statistically significant difference between genders for the distance AbMF, with tendency towards greater values for males. Group D showed that MF was more frequently located at the area of the 2nd premolars (65.9%), while the area of the 1st premolars was that of smallest frequency (4.9%). Conclusion: the edentulism only reduced the dimension of MF opening. Edentulous males had a greater MF opening than edentulous females. Keywords: Cone beam computed tomography; Mandible; Anatomy, Regional; Anatomic variation.